Disruption of the Cys5-Cys7 disulfide bridge in the platelet glycoprotein Ibβ prevents the normal maturation and surface exposure of GPIb-IX complexes - González-Manchón, Consuelo; Butta, Nora; Iruín, Gema; Alonso, Sonia; Ayuso, Matilde S.; Parrilla, Roberto (Thrombosis and Haemostasis, 2003)
This work aimed at elucidating the molecular genetic defect in two related patients with Bernard-Soulier syndrome (BSS) phenotype. Flow cytometric analysis revealed undetectable levels of platelet glycoproteins (GP), Ibα and IX, although plasma glycocalicin was detectable in both cases. The complete sequencing of GPIbα, GPIbβ, and GPIX revealed the presence of a single point mutation, a G to A substitution, in codon 30 of GPIbβ, that changes Cys5 to Tyr. The parents and sibling of the patients, heterozygotes for this mutation, were asymptomatic and they all showed a reduced platelet content of GPIbα and GPIX. Transient transfection of the mutant GPIbβ subunit failed to render surface expression of GPIbα and exerted a dominant-negative effect on the surface exposure of the GPIb-IX complex. Metabolic labelling and immunoprecipitation analysis of transfected cells indicated that [5Tyr]GPIbβ may associate with GPIX and GPIbα, but the maturation of the GPIb-IX complex is impaired. Substitution of either Cys5 or Cys7 by Ala failed to show surface expression of GPIb-IX, suggesting that the Cys5-Cys7 disulfide loop in GPIbβ is essential for the efficient processing and trafficking of GPIb-IX complexes toward the plasma membrane. Our findings indicate that the identified novel GPIbβ mutation is responsible for the BSS phenotype of the patients and provide an explanation for the molecular mechanism underlying the reduced platelet content of GPIb-IX complex in the heterozygous individuals.
Keywords: Gene mutations; inherited/acquired platelet disorders; platelet physiology; protein trafficking; protein structure/folding